Socoh of the Judean Shephelah The 2010 Survey - Hasel, Michael G. (Penn State University Press, 2021)
This is the first monograph dedicated to the site of Socoh in the Judean Shephelah. Our research was initiated in 2010 as an intensive survey by the Institute of Archaeology, Southern Adventist University, and the Institute of Archaeology, The Hebrew University of Jerusalem. The study incorporates historical sources that are listed and analyzed, including the Bible, ancient Near Eastern, Byzantine, and Medieval records. A history of the research conducted over the past 190 years by explorers, geographers, and archaeologists is compiled, before providing the full report on the results of an intensive site survey conducted at Socoh in 2010. Finally, specialized studies of the finds and a report of recent salvage excavations of burial caves, looted by antiquity robbers nearby, give a state-of-the-art presentation of the latest information known about this important biblical site in southern Judah